Isolation of a potentially arsenic-resistant Halomonas elongata strain (ml10562) from hypersaline systems in the Peruvian Andes, Cusco - Shirly Pila-Lacuta; David Pauccar; Jorge Rojas-Vargas; Ulises E. Rodríguez-Cruz; José Luis Sierra; Hugo G. Castelán-Sánchez; María Antonieta Quispe-Ricalde (PLoS ONE, 2025)
Halomonas elongata strain ml10562, was isolated from hypersaline that was collected from Acos Peru. Average Nucleotide Identity (ANI) and dDDH (digital DNA-DNA Hybridization) values between strain ml10562 and type strains of Halomonas elongata species were 71.0–78.4% and 18.8–21.5%, respectively. The draft genome, spanning 4,075,440 base pairs, has a GC content of 64.2% and contains 3,912 genes. Functional characterization revealed the strain’s ability to tolerate and resist increasing concentrations of sodium arsenate, with a minimum inhibitory concentration of 25 mM. Bioinformatic analysis revealed the presence of two operons, arsR-arsH-arsB and arsJ-gapdh-arsC, in the genome of strain ml10562, which could play a crucial role in arsenic resistance through transporter-mediated mechanisms. Overall, these results emphasize the potential adaptability of H. elongata ml10562 to arsenic-containing environments and extend our understanding of bacterial arsenic resistance mechanisms, allowing promising applications in bioremediation.